Women's Earning Power and the "Double Burden" of Market and Household Work - Natalie Chen; Paola Conconi; Carlo Perroni (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Bargaining theory suggests that married women who experience a relative improvement in their labour market position should experience a comparative gain within their marriage. However, if renegotiation possibilities are limited by institutional mechanisms that achieve long-term commitment, the opposite may be true, particularly if women are specialized in household activities and the labour market allows comparatively more flexibility in their labour supply responses. Evidence from the German Socio-Economic Panel indeed shows that, as long as renegotiation opportunities are limited, comparatively better wages for women exacerbate their 'double burden' of market and household work.
Keywords: D1; J2; J3; 330; bargaining; marriage and renegotiation